Frequency of Atrioventricular Block in Patients with Acute ST Segment Elevation Myocardial Infarction - Khan, Asad Ali; Ghaffar, Rahmat (Biological and Clinical Sciences Research Journal, 2025)
Atrioventricular (AV) block is a recognized complication of acute ST-segment elevation myocardial infarction (STEMI), associated with adverse clinical outcomes. The timely identification of conduction abnormalities can assist in risk stratification and management of affected patients.. Objective: To determine the frequency of atrioventricular block in patients with acute ST-segment elevation myocardial infarction. Methodology: We conducted this cross-sectional study on 104 patients aged 35 to 75 years of either gender presenting with acute STEMI (based on symptoms and ECG criteria). We determined the frequency of atrioventricular block in these patients. AV block was diagnosed through ECG (PR interval >0.20 seconds). Results: Mean age was 57.34±10.86 years. Fifty-eight (55.8%) were male and 46 (44.2%) were female. Nineteen (18.3%) patients had diabetes. Twenty-five (24.0%) had hypertension. Smoking was reported in 16 (15.4%) patients. The frequency of atrioventricular block in our study was 7 (6.7%). Conclusion: The frequency of atrioventricular block in patients with acute ST-segment elevation myocardial infarction in our study was 7 (6.7%).